2022
DOI: 10.29081/gsjesh.2022.23.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Corelations Between Biological Growth and Motor Capacities of Primary School Children

Abstract: The sample comprised in the research was represented by 57 students (29 girls (145.4±7.28 cm, 38.97±9.89 kg)) and 28 boys (143±6.55 cm, 38.61±8.22 kg)), aged between 10 – 12 years old. The types of measurements included in the study were as follows: anthropometrical measurements and biomotor measurements (standing long jump, abdominal endurance, motion velocity, and resistance). Results. Among girls, the analysis of Pearson’s correlation between the series of results indicates significant connectionsbetween th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…can be explained by physiological differences between genders, but the period of biological development in which they are in should not be omitted [17,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…can be explained by physiological differences between genders, but the period of biological development in which they are in should not be omitted [17,23].…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive epidemiological studies on the physical education of young people have consistently reported that male subjects are more active than female subjects and that physical activity decreases with age 18, respectively 24 [16], [21]. This can be explained by physiological differences between the sexes, but the period of biological development in which they are in should not be overlooked [17,18,19].…”
Section: Resultsmentioning
confidence: 99%